Privilege, Agency and Affect Understanding the Production and Effects of Action - Maxwell, Claire; Aggleton, Peter; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Drawing on a range of theoretical perspectives and engaging with new empirical evidence from around the world, this collection examines how privilege, agency and affect are linked, and where possibilities for social change might lie.
Keywords: Education; Educational sociology; Gender identity in education; Social structure; Social inequality; Education and sociology; Sociology, Educational; Social sciences -- Philosophy; Personality; Social psychology; Education; Sociology of Education; Gender and Education; Social Structure, Social Inequality; Sociology of Education; Social Theory; Personality and Social Psychology